PANDANGAN ISLAM TENTANG FUNDAMENTALISME: ANALISIS TAFSIR MAUDHU'I - Syifa Mulyani; Syahira Siti Nurazizah; Zaim Rozin Jamaludin; Shalahuddin Al Ayubbi (Melati Institute, 2023)
This paper discusses Islam and fundamentalism. This research uses descriptive methodology and maudhu'i interpretation. In our research we used a quantitative research methodology with secondary data sources, namely literature related to the research topic taken from books, journal articles, and other sources. In Indonesia, fundamentalism is rarely found because fundamentalists interpret verses or sacred texts textually (innerly) which characterizes religious ideology extremism. The author believes is related to the topic being discussed. Islam teaches us fellow creatures to love one another and oppose acts of violence and radicalism as justified by fundamentalism.